Results on photo identification for beluga whale Delphinapterus leucas in the Anadyr estuary of the Bering Sea - Ekaterina A. Prasolova; Roman A. Belikov; Andrey A. Ryabov; Denis I. Litovka (Известия ТИНРО)
Definition of individual beluga whales by the method of photo identification and selection of the main types of markers are presented for beluga whales in the Anadyr estuary, western Bering Sea. The study was conducted in the aggregation of beluga whales in three different sites at Anadyr - in the Anadyr sea port and at ferry docks № 8 and № 10 in the period from August 14 to September 6, 2013 (summer feeding of the whales). The maximum number of whales (40-70 animals) was observed at the ferry dock № 10, 2-6 whales were at the ferry dock № 8, and 1-2 ones - at the port. Mother-calf pairs were observed in all sites, but the portion of adult whales was the highest at the ferry dock № 10. Photocamera Nikon D90 and Nikkor lens (70-200 mm) were used for the photo ID. Mechanical skin damages, infections, spinal ridge traces, and age spots were used as individual markers. In total, 4400 images were obtained, including 155 ones with sides of beluga whales. The markers were observed both on the left side (32 cases) and right side (97 cases) of the whales, but both sides were identified for 13 whales only, including 3 females with calves. Taking into account the risk of reassessment in case of using two sides for identification, the identification is considered as successful for 110 individuals of beluga whale. Almost all identified individuals were met only once during the whole period of observation, only 6 of them were met twice, and only 4 - three times. One whale appeared 3 days in a row: on August 16, 17 and 18, and 5 individuals came 2 days in a row. Such few recurrent meetings may indicate a weak fidelity of beluga whales to certain water areas in the estuary, though maybe the length of study is insufficient, taking into account that a strong fidelity of mother-calf pairs of beluga whales to certain areas of the Anadyr estuary, considered as their hunting areas, was determined by visual observations of Shirshov Institute of Oceanology in the 1980s. Probably, the area at the dock № 10, where the whales form large aggregation, is not assigned to individual animals but is a common feeding area. This large aggregation is similar to the aggregation of beluga whales at Cape Beluzhy of Solovetsky Island in the White Sea. However, these aggregations are fundamentally different by their nature: the reproductive aggregation at Solovetsky Island is distinguished by various forms of social interactions, including sexual activity, while the search and hunting behavior prevail in the feeding aggregation at the ferry dock № 10. The main reason for the beluga whales concentration in this area is dense concentration of freshwater fish and salmons migrating for spawning. Reproductive aggregations of beluga whales are not known yet in the Far-Eastern Seas.